Comparison of Palm Oil Growers PIR-BUN program and Non PIR-BUN in Kenagarian Manggopoh, Lubuk Basung Subdistrick Agam District. - Oktavia, Melisa - (STKIP PGRI Sumbar, 2014)
This study aims to determine Comparative data on Palm Oil Growers Program and NonPIR PIR-BUN-BUN in Kenagarian Manggopoh Lubuk Basung Subdistrick Agam District: 1) Thedifference in the processing of oil palm land, 2) Differences in seeding and planting, 3) Thedifference in maintenance palm oil, 4) difference palm oil yield and 5) marketing difference.The research is a comparative descriptive. The study population was a palm oil farmerPIR-BUN program and oil palm farmers Non PIR-BUN in Nagari Manggopoh totaling 912farmers. The sample in this study were taken with a proportional random sampling technique witha proportion of 10% of each population so that the sample was 91 families of farmers.Results of the study found that: (1) There is no difference between the land preparationfor oil palm farmers PIR-BUN with palm oil farmers Non-PIR-BUN, (2) There is no differencebetween the nursery and the planting of oil palm farmers Farmers PIR-BUN with palm Non-PIRBUN,(3) There were no differences between the maintenance of oil palm smallholders PIR-BUNwith palm oil farmers Non-PIR-BUN, (4) There is no difference between the palm oil of oil palmgrowers PIR-BUN with farmers palm oil Non-PIR-BUN, (5) There is no difference betweenfarmers palm marketing PIR-BUN with palm oil farmers Non-PIR-BUN.